PURPOSE - Kahlen, A.D. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: Opportunities to improve production processes and access to markets through the implementation of lean manufacturing in biomedical manufacturing are presented. The importance of a unified definition of manufacturing, to which biomedical manufacturing is party, is emphasized, and the theory of